Esp1396I restriction–modification system: structural organization and mode of regulation - Česnavičienė, Eglė (Oxford University Press, 2003)
Esp1396I restriction–modification (RM) system recognizes an interrupted palindromic DNA sequ ence 5′-CCA(N)(5)TGG-3′. The Esp1396I RM system was found to reside on pEsp1396, a 5.6 kb plasmid naturally occurring in Enterobacter sp. strain RFL1396. The nucleotide sequence of the entire 5622 bp pEsp1396 plasmid was determined on both strands. Identified genes for DNA methyltransferase (esp1396IM) and restriction endonuclease (esp1396IR) are transcribed convergently. The restriction endonuclease gene is preceded by the small ORF (esp1396IC) that possesses a strong helix-turn-helix motif and resembles regulatory proteins found in PvuII, BamHI and few other RM systems. Gene regulation studies revealed that C.Esp1396I acts as both a repressor of methylase expression and an activator of regulatory protein and restriction endonuclease expression. Our data indicate that C protein from Esp1396I RM system activates the expression of the Enase gene, which is co-transcribed from the promoter of regulatory gene, by the mechanism of coupled translation.